Abnormal large-scale resting-state functional networks in anti-N-methyl-D-aspartate receptor encephalitis - Gong, Xiarong; Wang, Libo; Guo, Yuanyuan; Ma, Yingzi; Li, Wei; Zhang, Juanjuan; Chen, Meiling; Wang, Jiaojian; Meng, Qiang; Chen, Kexuan; Tian, Yanghua (Frontiers in Neuroscience, 2024)
Patients with anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis often experience severe symptoms. Rs-fMRI has revealed widespread impairment of functional networks in patients. However, the changes in information flow remain unclear. This study aims to investigate the intrinsic functional connectivity (FC) both within and between resting-state networks (RSNs), as well as the alterations in effective connectivity (EC) between these networks.Resting-state functional MRI (rs-fMRI) data were collected from 25 patients with anti-NMDAR encephalitis and 30 healthy controls (HCs) matched for age, sex, and educational level. Changes in the intrinsic functional connectivity (FC) within and between resting-state networks (RSNs) were analyzed using independent component analysis (ICA). The direct functional interaction between RSNs was identified by granger causality analysis (GCA).Compared to HCs, patients with anti-NMDAR encephalitis exhibited lower performance on the Wisconsin Card Sorting Test (WCST), both in terms of correct numbers and correct categories.Additionally, these patients demonstrated decreased scores on the Montreal Cognitive Assessment (MoCA). Neuroimaging studies revealed abnormal intra-FC within the default mode network (DMN), increased intra-FC within the visual network (VN) and dorsal attention network (DAN), as well as increased inter-FC between VN and the frontoparietal network (FPN). Furthermore, aberrant effective connectivity (EC) was observed among the DMN, DAN, FPN, VN, and sensorimotor network (SMN).Patients with anti-NMDAR encephalitis displayed noticeable deficits in both memory and executive function. Notably, these patients exhibited widespread impairments in intra-FC, inter-FC, and EC.These results may help to explain the pathophysiological mechanism of anti-NMDAR encephalitis.